Cannabis use by women during pregnancy does not influence infant DNA methylation of the dopamine receptor DRD4 - Fransquet, P.; Hutchinson, D.; Olsson, C.; Allsop, Steve; Elliott, E.; Burns, L.; Mattick, R.; Saffery, R.; Ryan, J. (2017)
Background: Maternal cannabis use in pregnancy is linked with long-term adverse behavioral outcomes in offspring. Epigenetic processes established in utero that affect dopaminergic (reward) signaling may mediate risks. Associations between cannabis use and offspring DNA methylation have not been investigated; however, maternal tobacco smoking in pregnancy is associated with distinct patterns of DNA methylation at birth and beyond. Objectives: To determine whether maternal cannabis use is associated with methylation of the dopamine receptor gene DRD4 promoter in infants. Methods: Mothers in the Triple B study provided detailed information on drug use in each trimester of pregnancy. Buccal swabs were collected from neonates at 8 weeks (n = 804, 51.7% male, and 48.3% female). DRD4 promoter DNA methylation was measured using SEQUENOM MassARRAY. Results: Fifty-seven of the women in the study reported drug use during pregnancy, of whom 44 used cannabis. Of 19 cytosine-phosphate-guanine dinucleotides (CpG) units tested in DRD4, gestational cannabis use was associated with offspring methylation at 1 CpG unit in multivariate models (ß + 1.48, CI: 0.02 to 2.93, and p = 0.047). At another site there was weak evidence that both cannabis and other drug use were independently associated with increased methylation, while the association with tobacco was in the reverse direction (cannabis use ß + 0.67, CI: -0.12 to 1.46, and p = 0.09; other drug use ß + 1.11, CI: 0.17 to 2.05, and p = 0.02; tobacco use ß -0.41, CI: -0.85 to 0.03, and p = 0.07). None of the associations would remain significant after correction for multiple testing. Conclusion: There is no strong evidence that maternal cannabis use in pregnancy is associated with offspring DRD4 methylation.